E-cigarette vaping is associated with pro-fibrotic gene expression in kidney and liver tissues - Wanjun Gu; Howard Chang; Poorvi Saini; Samvel Gaboyan; Jarod Olay; Jorge A. Masso-Silva; John Shin; Ira Advani; Ashley Du; Cameron Brand; Joan Heller Brown; Alexia Perryman; et al. (Journal of Molecular Medicine, 2026)
Conventional tobacco use causes a wealth of diseases and adversely affects cells and organ systems across the body. The long-term effects of e-cigarette vaping on the same remain unclear. Identifying early pathogenic signals at the organ level via animal models may shed light on potential downstream effects in humans. Here we investigate transcriptomic changes in the kidney and liver, organs known to be damaged by long-term combustible tobacco use, of mice exposed daily to e-cigarette aerosols (vapor) with or without nicotine. C57BL/6 male 6–8 week-old mice underwent whole-body exposure to room air, e-cigarette (3rd generation box mod) vapor containing 70:30 propylene glycol and glycerin (PG: Gly) without nicotine (Vehicle), and e-cigarette vapor with 6 mg/mL freebase nicotine in 70:30 PG: Gly (E-cig) for 1 h daily for 3 months. RNA sequencing on kidney and liver tissues and apriori gene set analysis were performed. Unbiased principal component analysis identified closer clustering of E-cig and Vehicle groups, relative to Air, in the kidney. Assessment of the a priori gene set found nicotine to be associated with greater transcriptomic changes in the kidney while vehicle chemicals induced greater changes in the liver. Alterations in expression of Car3 and Foxo3 identify oxidative stress and inflammation in the renal system associated with e-cigarette exposure, while dysregulated Il6ra and Lpin1 in the liver highlight disruptions in lipid metabolism and immune signaling. Chronic inhalation of e-cigarette vapor alters gene expression in downstream organs, in a pattern most consistent with promotion of fibrosis and metabolic dysregulation, underscoring the need to define long-term pathophysiologic effects of e-cigarette vaping across the body.